Gastrodiplomacy: International Experiences and Policy Implications for Vietnam in Strengthening Cultural Diplomacy - Thanh An, Tran (VNU Journal of Science: Policy and Management Studies; Vol 41 No 1DO - 10.25073/2588-1116/vnupam.4543, 2025)
Gastrodiplomacy plays a crucial role in cultural diplomacy, contributing to national branding, promoting tourism, and expanding the export market for food products. Many countries worldwide have developed systematic strategies to enhance their culinary identity on the global stage, linking gastronomy with cultural and tourism promotion. In Vietnam’s foreign affairs, cultural diplomacy constitutes a key pillar of comprehensive diplomacy, with cuisine serving as a distinctive expression of national heritage. Despite its rich and diverse culinary tradition, Vietnam has yet to establish a comprehensive strategy to maximize its potential. To address this gap, a cohesive policy framework is essential-one that supports businesses and the overseas Vietnamese community, expands the scale of international food festivals, and enhances promotion through digital platforms. A well-structured gastrodiplomacy strategy will not only elevate Vietnamese cuisine on the global map but also strengthen cultural diplomacy, fostering peace and friendship among nations. This paper examines the concept of gastrodiplomacy and its role in advancing cultural diplomacy. Drawing from international experiences, it further proposes policy recommendations to enhance Vietnam’s cultural diplomacy through the development of gastrodiplomacy initiatives in the contemporary context.